Osaka follies - Isozaki, Arata 1931-2022; Price, Cedric 1934-2003; Taki, Kōji 1928-2011 (Architectural Association, 1991)
This publication has been produced to accompany an exhibition of original drawings, models and photographs of the Osaka Follies held at the Architectural Association in London from 8 February to 22 March 1991. The exhibition and publication have been jointly arranged by the Architectural Association in London and Workshop for Architecture and Urbanism in Tokyo. Arata Isozaki was General Producer of the International Garden and Greenery Exposition, Osaka, Japan, 1990; Hajime Yatsuka was Executive Co-ordinating Architect. The folly projects were co-ordinated by Kayoko Ota, Atsuko Mizobuchi, Midori Hammura and Akira Suzuki of Workshop for Architecture and Urbanism. Financial support for the Tokyo symposium was provided by Toyo Sash Co., Ltd. The architects of the follies were selected by Arata Isozaki and the late Chairman of the AA, Alvin Boyarsky. The exhibition has been organized by the Chairman's assistant, Micki Hawkes. Osaka Follies has been produced for AA Publications by Pamela Johnston (production editor) and Dennis Crompton (technical co-ordinator), through the AA Print Studio with Annie Bridges, Ann Cheatle, Stuart Smith, Marilyn Sparrow, Gail Tandy and Mary Wall. Exhibition mounting supervisor: Katherine Jacobs. The photographs in this publication were specially commissioned from Hélène Binet, with the exception of the following: 30, 33, 38, 39, 42 centre (Koji Kobayashi); 32 (Tomasz Samek); 82 (Tom Bonner); 141, 142, 143 (Gigantes & Zenghelis). The illustration on page 6 is taken from Twenty-one Views of Congleton and Neighbourhood published by Robt. Head.